2017
DOI: 10.1038/srep41016
|View full text |Cite
|
Sign up to set email alerts
|

Listeners can extract meaning from non-linguistic infant vocalisations cross-culturally

Abstract: We present empirical evidence showing that the acoustic properties of non-linguistic vocalisations produced by human infants in different cultures can be used cross-culturally by listeners to make inferences about the infant’s current behaviour. We recorded natural infant vocalisations in Scotland and Uganda in five social contexts; declarative pointing, giving an object, requesting an action, protesting, and requesting food. Using a playback paradigm, we tested parents and non-parents, who either had regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This difference is already visible in human infants before language: from about four months of age, humans begin to control their vocal apparatus, first by engaging in playful babbling, then followed by the production of simple word-like structures. At the same time, human infants produce nonlinguistic vocalizations for social communication [4], very similar to what has been reported in non-human primates [5]. Human babbling has a social bonding function, possibly evolved in response to cooperative breeding [6], but it also provides the scaffolding for increasing vocal control and competence for subsequent speech production.…”
Section: Introductionsupporting
confidence: 71%
“…This difference is already visible in human infants before language: from about four months of age, humans begin to control their vocal apparatus, first by engaging in playful babbling, then followed by the production of simple word-like structures. At the same time, human infants produce nonlinguistic vocalizations for social communication [4], very similar to what has been reported in non-human primates [5]. Human babbling has a social bonding function, possibly evolved in response to cooperative breeding [6], but it also provides the scaffolding for increasing vocal control and competence for subsequent speech production.…”
Section: Introductionsupporting
confidence: 71%
“…Our aim here was to demonstrate the validity of applying the nonhuman ape method to human children, to explore any possible use of the great-ape repertoire of gestures. In order to reduce bias created by culturally- or environmentally-specific features of a specific human population, as well as collecting data specifically for this study (Göttingen, Germany), we incorporated opportunistic coding of an existing data collected as part of an observational study investigating children’s everyday interactions with their caregivers in Masindi, Uganda (see Kersken et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…German children make up a typical WEIRD sample (Henrich et al 2010a, b; Hwang 2013; Keller and Kärtner 2013; Henrich 2015), in comparison Ugandan children grow up in larger family groups and often have siblings and other young relatives as primary contacts. Furthermore, studies observed lower rates of triadic interaction between the child, a parent or caregiver, and an object or event in the environment in Ugandan children (Kersken et al 2017, see also; Britto et al 2013; Salomo and Liszkowski 2013; Kärtner et al 2010; Keller et al 2005; Rabain-Jamin et al 2003; Ainsworth 1967). Given the small sample from our two populations our goal is not to engage in cross-cultural comparison; instead we incorporate both populations to provide a more culturally diverse dataset in order to better start to describe any species-typical human behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on human listeners’ perception of behavioural contexts from nonverbal vocalisations are limited to investigations of vocalisations produced by infants and non-human animals. This research has shown that listeners can match infant vocalisations to production contexts like requesting food and giving an object (Kersken et al, 2017 ), and parents can infer contexts like interaction with the caregiver (play) and satisfaction after feeding from vocalisations of infants (Lindová et al, 2015 ). Human listeners can also accurately infer situational information from vocalisations of other species, including domestic piglets (Tallet et al, 2010 ), dogs (Pongrácz et al, 2005 ; Silva et al, 2021 ), cats (Nicastro & Owren, 2003 ), macaques (Linnankoski et al, 1994 ), and chimpanzees (Kamiloğlu et al, 2020 ).…”
Section: Perception Of Behavioural Contexts From Nonverbal Vocalisationsmentioning
confidence: 99%